Mean And Diffrential Torque Control Using Hysteresis Current Controller For Dual PMSM Drives - Mat Lazi, Jurifa; Ibrahim, Zulkifilie; Sulaiman , Marizan (Little Lion Scientific Islamabad Pakistan, 2011)
-